Developmental Changes in Time and Space Promote Evolutionary Diversification of Flowers: A Case Study in Dipsacoideae - Naghiloo, Somayeh; Claßen-Bockhoff, Regine (Frontiers in Plant Science, 2017)
Diversification in flower shape and function is triggered by the high plasticity of flower meristems. Minute changes in space and time can profoundly affect the formation of adult structures. Dipsacoideae provides an excellent model system to investigate the evolutionary aspects of temporal and spatial changes in flower development due to its small size, the resolved phylogenetic framework, and significant diversity of perianth form and merosity. In the present study, we investigate the sequence of floral organ initiation and quantify the interactions between flower meristem expansion and petal primordium size in eight species representing two major clades of Dipsacoideae. Our quantitative study indicates the plasticity of flower meristem for regulating pentamery either due to a decrease in petal primordium size (Scabiosa) or an increase in flower meristem size (Pterocephalus and Lomelosia) compared to tetramerous flowers. According to our results, temporal shifts of organ initiation during flower evolution contribute to the morphological diversity of perianth. Sepal reduction in members of the Dipknautids is paralleled with a delay in sepal initiation. The multiplication of sepals in Lomelosia and Pterocephalus is correlated with an extension of initiation time. Some heterochronies in early development do not affect adult morphology. The effects of a temporal change in early development can be enhanced, reduced, or eliminated by later changes of the growth rate during development. Our results confirm the hypothesis that the interaction between timing and space plays an important role for evolutionary diversification of flowers.